Microanatomical and Biochemical Influences of Lycopene on The Renal Status in Streptozotocin-Induced Diabetic Wistar Rats - Arayombo Babatunde Elijah; Solomon Bolade Arayombo (Majalah Biomorfologi, 2025)
Highlights:1. The histoarchitecture of the kidney revealed significant derangements in the renal tissue, such as widening of the urinary space and loss or effacement of podocytes and mesangial cells, which were restored to near normal in the treated groups. 2. The biochemical parameters such as blood glucose, insulin, and antioxidant levels in this study were observed to be altered in the diabetic groups, but with administration of the intervening agent, these biochemical parameters were normalized. 3. The intervening agent was found to be a better prophylactic than curative therapy.   Abstract Introduction: Chronic hyperglycemia is pathognomonic of diabetes mellitus; however, this is not responsible for many of the morbidities. Blood glucose is fairly readily regulated by drugs; however, this is not inhibiting the long-term complications despite euglycemic control, there is still damage in virtually every organ system. Hence, this study evaluated the beneficial effect or otherwise of lycopene on the histoarchitectural and biochemical layout of the kidney in diabetic wistar rats. Objective: To assess the histoarchitecture and biochemical parameters  of the kidney of diabetic Wistar rats after intervention with lycopene as well as to determine whether lycopene is more efficacious as curative than prophylactic agent. Materials and Method: The rats were grouped into five sects (a, b, c, d, and e) of six animals per group. Group a is the normal control that was given 2ml/kg/day of citrate buffer per oral for 30 days. Group b was given 60mg /kg of streptozotocin. Group c was treated with lycopene 20mg/kg/day p.o for 30 days after diabetes induction. Group d is the group that was pretreated with lycopene 20mg/kg/day orally for 30 days. Group e was treated with Insulin 5 IU/kg for 30 days after diabetes induction. The rats were sacrificed under ketamine anaesthesia at the end of the experiment. Result: The histological outline of the kidney revealed significant widening of the urinary space in the untreated diabetic group (b) and the test groups (c and d) when compared with the normal control group (a). It was observed that  the blood glucose levels in the test groups significantly reduced in value (p<0.05) below diabetic range. There was significantly higher level (p<0.05) of antioxidants in the curative than the prophylactic group, Conclusion: This study showed that lycopene conferred better ameliorative effect when used prophylactically than curatively.